Biodiversity Mainstreaming for Healthy and Sustainable Food Systems - A toolkit - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The tool was launched in 2018 at the Conference of the Parties to the Convention on Biological Diversity.